Big business and fascism a dangerous collusion - Poruthiyil, Prabhir Vishnu (2021)
Anxieties stemming from rising inequalities have led significant sections of the world’s population to reject democratic practices and place their trust in politicians with fascist tendencies who promise to wrest control of their destinies from elites. Ironically, elite interests, far from being threatened, are bolstered by the rise of fascism, as discredited democratic institutions can be dismantled with impunity. The emerging alliance between the neoliberal project and fascist politics is a phenomenon that the business and society scholarship is ill-equipped to confront as it remains trapped in the same neoliberal pro-elite paradigms that neglect meaningful attention to material (in)equality and focus instead on ensuring a minimum floor of rights required for subsistence. Neglecting the concentration of wealth among the elite, particularly in countries with historic legacies of inequalities based on race, caste, ethnicity, and religion, creates ideal conditions for the eruption of fascisms premised upon programmatic denial of the full range of civil rights to one or more sections of the population, so that even the floor minimum becomes impossible to achieve for all. This paper argues that corporate collusions with fascism can be challenged only by a commitment to redistribution of wealth and creating critical citizens and by generating knowledge that can question authority: in other words, scholarship must become a subversive activity.
Keywords: civil liberties; Fascism; Lynching; Aufsatz in Zeitschrift